TIME-RESOLVED LUMINESCENCE OF FE3+ AND MN2+ IONS IN HYDROUS VOLCANIC GLASSES - Zotov N.; Yanev Y.; Piriou B. (My University, 2002)
Time-resolved luminescence spectra of natural and synthetic hydrous volcanic glasses with different colors and different Fe, Mn, and H2O content were measured, and the implications for the glass structure are discussed. Three luminescence ranges are observed at about 380–460, 500–560, and 700–760 nm. The very short-living (lifetimes less than 40 ns) blue band (380–460 nm) is most probably due to the 4T2(4D) →6A1(6S) and 4A1(4G) →6A1(6S) ligand field transitions of Fe3+. The green luminescence (500–560 nm) arises from the Mn2+ transition 4T1(4G) →6A1(6S). It shows weak vibronic structure, short lifetimes less than 250 μs, and indicates that Mn2+ is tetrahedrally coordinated, occupying sites with similar distortions and ion–oxygen interactions in all samples studied. The red luminescence (700–760 nm) arising from the 4T1(4G) →6A1(6S) transition of Fe3+ has much longer lifetimes of the order of several ms, and indicates that ferric iron is also mainly tetrahedrally coordinated. Increasing the total water content of the glasses leads to quenching of the red luminescence and decrease of the distortions of the Fe3+ polyhedra.
Keywords: Hydrous glasse; Fe3+ luminescence; Mn2+ luminescence